The effect of psychological manipulations on the development of secondary hyperalgesia: a critical review - Elke Meyers; Delia Della Porta; Diana M. Torta; Emanuel N. van den Broeke (PAIN Reports)
Abstract. As central sensitization is believed to contribute to persistent pain and psychological factors are increasingly acknowledged to play a role as well, the question arises of whether psychological factors can modulate the development of central sensitization. Secondary hyperalgesia is thought to be a manifestation of central sensitization and can be induced experimentally in humans. To define the state-of-the-art, we critically reviewed the existing evidence that psychological factors can influence the development of experimentally induced secondary hyperalgesia, a proxy of central sensitization. We retrieved 23 studies, 17 aimed at modulating the development of secondary hyperalgesia, 4 at modulating hyperalgesia when already established, and 2 observational studies. The psychological interventions in the 17 included papers focused on placebo/nocebo interventions (N = 5), attention and cognitive load (N = 6, 7 experiments), social support (N = 1), cognitive behavioral therapy (N = 1), threat/fear induction (N = 2), and emotional disclosure (N = 1). Interventions were considered effective if they successfully decreased or increased the magnitude and/or spatial extent of secondary hyperalgesia. Although some psychological manipulations might interfere with the development of secondary hyperalgesia, the number of studies is too low to draw firm conclusions. More studies and replications are needed to determine the impact of psychological factors on the development of secondary hyperalgesia. Factors that should be considered in future studies are (among others) the risk of bias, sufficient statistical power, the measurement of secondary hyperalgesia, the choice of sensitization protocol, the strength of the manipulation, and the role of sex.